THE USE OF CONJUNCTIONS IN HIGH SCHOOL STUDENTS’ DESCRIPTIVE PARAGRAPHS - Alfonsa Saskia Ardanellia; Truly Almendo Pasaribu (Elite : English and Literature Journal, 2019)
Conjunctions connect words or phrases of semantic units to guide the writing and reading process. This study aimed at examining EFL learners’ use of conjunctions in writing descriptive texts. This study analyzed (1) the use of conjunctions in students’ descriptive texts and (2) the errors of using conjunctions. The study involved forty-four students’ descriptive texts which were analyzed using a qualitative descriptive method using Halliday and Hasan’s taxonomy (1976) as well as Ong’s framework (2011). We found 417 conjunctions which are classified into additive conjunctions (71.22%), the most common conjunctions used by the students, temporal conjunctions (13.43%), adversative conjunctions (11.99%), and causal conjunctions (3.36%).The predominance of additives denotes that the students added information in describing people. Although the students use these four types of conjunctions, some conjunctions are used inappropriately. We found the errors of conjunctions: misuse errors (42.55%), unnecessary addition errors (40.43%), omission errors (8.51%), and redundant repetition (8.51%). The study of discourse markers is relevant for designing writing materials for EFL students. Teachers can help students enhance their writing through various exposures of different discourse markers with their pragmatic functions.ABSTRAK Konjungsi (kata sambung) menghubungkan kata atau frasa unit semantik untuk yang dapat memudahkan proses penulisan dan membaca. Konjungsi membantu pembaca mengaitkan satu ide ke ide berikutnya. Penelitian ini bertujuan untuk menggali penggunaan konjungsi peserta didik Bahasa Inggris dalam menulis teks deskriptif. Penelitian ini menganalisis (1) penggunaan konjungsi dalam teks deskriptif yang ditulis oleh siswa SMA dan (2) kesalahan dalam penggunaan konjungsi. Penelitian ini melibatkan empat puluh empat teks deskriptif yang dianalisis menggunakan metode deskriptif kualitatif menggunakan taksonomi Halliday dan Hasan (1976) serta kerangka kerja Ong (2011). Peneliti menemukan 417 konjungsi yang diklasifikasikan menjadi konjungsi aditif (71,22%), konjungsi yang paling umum digunakan oleh siswa, konjungsi temporal (13,43%), konjungsi adversatif (11,99%), dan konjungsi kausal (3,36%). Konjungsi aditif menunjukkan bahwa siswa dapat menambahkan informasi tambahan ketika mendeskripsikan orang dalam bentuk paragraf. Meskipun siswa menggunakan keempat jenis konjungsi, beberapa konjungsi digunakan secara tidak tepat. Para peneliti menemukan kesalahan, yaitu: kesalahan penyalahgunaan (42,55%), kesalahan penambahan yang tidak perlu (40,43%), kesalahan kelalaian (8,51%), dan pengulangan yang berlebihan (8,51%). Penelitian tentang penanda wacana ini relevan untuk pembelajaran keterampilan menulis. Pendidik dapat membantu siswa menggunakan konjungsi yang beragam mereka dengan memberi banyak contoh penanda wacana serta fungsi pragmatis mereka.Kata Kunci: Kata Sambung, Paragraf Deskriptif, Menulis, Analisis Kesalahan